2003
DOI: 10.1067/mtc.2003.79
|View full text |Cite
|
Sign up to set email alerts
|

Video-assisted multivessel revascularization through a left anterior small thoracotomy approach with the Symmetry Aortic Connector System

Abstract: We have demonstrated a potential advantage of the sutureless Symmetry Aortic Connector System as a suitable approach that affords minimal access. Video-assisted multivessel revascularization through a left anterior small thoracotomy approach with an automated mechanical anastomosis device is particularly useful in patients undergoing coronary artery bypass reoperations or those at risk of poor sternal healing or infection. This approach seems to be a safe alternative to standard median sternotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
1

Year Published

2004
2004
2008
2008

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…Kinking of the graft has been mentioned as a possible reason for the high incidence of graft occlusion with the SACS. 2,3,22 This is possible because the aortic connector is anastomosed at a 90°angle to the ascending aorta. Kinking can also be caused by an excessively long bypass graft inasmuch as, with mechanical anastomoses, unlike conventional ones, the proximal anastomosis must be created first, and so the length of the graft may be incorrectly estimated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kinking of the graft has been mentioned as a possible reason for the high incidence of graft occlusion with the SACS. 2,3,22 This is possible because the aortic connector is anastomosed at a 90°angle to the ascending aorta. Kinking can also be caused by an excessively long bypass graft inasmuch as, with mechanical anastomoses, unlike conventional ones, the proximal anastomosis must be created first, and so the length of the graft may be incorrectly estimated.…”
Section: Discussionmentioning
confidence: 99%
“…Results of short-and midterm follow-up studies on the patency rate of these devices are controversial, with some reports showing good results and some an incidence of graft occlusion as high as 50% with the SACS. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Long-term follow-up studies are still lacking; so far, the longest mean follow-up period was reported by Kitamura and associates 17 in October 2005. Twenty-seven SACSs were evaluated with multislice computed tomography (MSCT) by that group; the mean follow-up was 19 months and the 1-year patency rate of that mechanical device was 92.6%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6] The second generation of connecting systems can safely and quickly construct the anastomosis, 7 which is especially attractive for off-pump procedures or even minimal-access CABG. 8 But acceptance of these products depends on the mid-and longterm patency rates. In this prospective, nonrandomized, multicenter study, we investigated the midterm patency rates and clinical outcome of the St. Jude Medical second-generation aortic connector (Symmetry G2).…”
mentioning
confidence: 99%
“…3 e 4). Questo accesso viene utilizzato anche in chirurgia cardiaca (rimozione di pacemakers infetti, chirurgia della valvola aortica e mitralica, rivascolarizzazione miocardica, reinterventi) in pazienti in cui sia indicato evitare la sternotomia [6][7][8][9][10].…”
Section: Minitoracotomia Videoassistitaunclassified